Incidence, molecular characterization and antibiotic resistance profile of Methicillin resistant staphylococcus aureus Isolated from clinical origin and associated surroundings in hospital - Marha, Faria (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2019.